Gastrointestinal foreign body in a banning tortoise (Manouria emys) at Bandung Zoo - Jerica , Monica Silva; Bernadette , Josephin; Anggitasari , Teresa Wening; Ramadan , Noval Ekarian; Mohamad , Kusdiantoro (ARSHI Veterinary Letters, 2025)
Turtles have the habit of swallowing foreign objects, known as geophagy. Swallowed foreign objects can obstruct the digestive tract. A banning tortoise (Manouria emys), male, weighing 13.5 kg, was reported to have decreased appetite, weakness, inability to defecate, and watery eyes. Physical examination and radiographic examination (X-ray) showed the accumulation of foreign objects in the digestive tract. The treatment was performed by installing a feeding tube, administering glycerin, and administering biodin. After treatment, the turtle expelled the foreign object in the form of sand during defecation and experienced an improvement in body condition. The turtle was active again and was declared cured after 18 d of treatment.